Dominant Physical Condition Components of Sepak Takraw Sport for Cimahi City Athletes - Andy Supriady (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2023)
The quality of physical condition is the foundation for developing an athlete's technique, tactics, strategy, and mentality. The purpose of this study was to determine the dominant physical condition components that support sepak takraw skills through measurement of physical aspects including strength, endurance, speed, agility, and flexibility of sepak takraw players. The method used in this research is descriptive quantitative by taking data using tests and measurements. The population and sample were seven Cimahi City sepak takraw athletes consisting of three male athletes and five female athletes. The instruments used for physical conditions are physical condition test items including speed, flexibility, balance, strength and endurance. The results showed that the speed component was in the very poor category (12.5%). In the flexibility component in the excellent category (12%). In the agility component in the excellent category (25%). In the strength component in the excellent category (25%). And in the power component in the poor category (25%). The research findings reveal that the dominant physical condition components are agility, balance and strength.